جدلية الموت والحياة في فنون الحضارات القديمة - روضان، حمدية كاظم (جامعة الكوفة - كلية التربية للبنات, 2016)
يولد الإنسان ويعيش وتتخذ حياته مسالك مختلفة وهو يسعى إلى تحقيق ذاته عبر نشاطه ويطمح إلى تأكيد وجوده والتمايز ضمن المجموع عبر نتاج فكره وجهده المتواصل في الحياة، والفن أحد أوجه العمل الإنساني وأحد سمات فكره يخضع لظروف ومتغيرات البيئة والمجتمع ولكنه يظل جزءًا من محاولات فهم الإنسان لوجوده ومصيره، والفنان والحضارة يولدان ويتطوران تحت ضغط فكرة الموت والحياة اللتان تصنعان نمط التفكير والحضارة والإبداع باعتبارهما الفضاء الذي يعمل فيه المفكرون والمبدعون بغية فهمه والوصول إلى أسراره. هكذا وتَلخَصت مشكلة البحث الحالي في إمكانية الإجابة عن التساؤلات التالية:- - كيف يكمن فهم جدلية الموت والحياة في فنون الحضارات القديمة؟ - ماهي الدوافع التي تقف وراء الإبداعات الفنية التي تمجد الحياة بعد الموت؟ - هل أسهمت الفنون في الحضارات القديمة في تشكيل صورة الموت والولادة ورسخت هذه الصورة في المجتمعات القديمة؟ وقد تضمن الفصل الأول من البحث تعريفاً بمشكلة البحث، أما أهمية البحث والحاجة إليه فقد تم تحديدها بما يلي:- -يقوم البحث على تتبع موضوعة الموت والولادة وكيفية تعامل الإنسان معها ودورها في بناء الحضارات القديمة وكيفية استخدام الموت كموضوعة وظفت في الفنون المعمارية والتشكيلية. -يقدم دارسة لأصول موضوعة الموت والولادة في النتاج الفلسفي. أما هدفا البحث فقد تم تحديدهما: -تعرف مفهوم الموت والحياة في الحضارات القديمة؟ الحدود المكانية- يتحدد البحث الحالي بدارسة فنون حضارة العراق القديم والحضارة المصرية القديمة، والحضارة الإغريقية. الحدود الزمانية- يتحدد البحث الحالي بدارسة للفترة من 3600 ق.م إلى 200 ق. م. الحدود الموضوعية- يتحدد البحث الحالي بدارسة فنون العمارة والنحت والخزف في الحضارات القديمة. وقد قامت الباحثة بتحليل أهم المصطلحات الواردة في البحث أما الفصل الثاني فقد اشتمل على ثلاثة مباحث الأول يمثل استعراضا للجذور التاريخية لفكرة الموت والحياة في الحضارات القديمة. أما المبحث الثاني فقد تناول الأسطورة وفكرة الموت والحياة أما المبحث الثالث فقد اشتمل على دارسة تمثيلات الموت والحياة في فنون الحضارات القديمة. أما الفصل الثالث فقد احتوى إجراءات البحث وتضمن، مجتمع البحث واختيار العينة وأداة البحث وتحليل العينة البالغة (9) نماذج. أما الفصل الرابع فقد أسفر عن النتائج والاستنتاجات ومنها: - أيقن الفكر العراقي القديم بعدم إمكانية الخلود وآمن بالموت كحقيقة مصيرية لكل البشر لذا لم يعمل من أجل ذاته بل من أجل الآخرين ومن أجل مبدأ الحياة نفسها. كما في النموذج (2،1). - صاحب الشعور بحتمية الموت نوع من الشعور بالعدمية والفوضى ولا جدوى الحياة وأدى في أغلب الأحيان إلى إقدام العراقيين القدماء على التضحية بمنجزات حضارية وعمرانية كبيرة انهارت وتحطمت ولم يتم الحفاظ عليها. - شعر المصريون القدماء بالأمان والاستقرار والهدوء والسكينة في بلادهم البعيدة المحصنة ضد الغزاة بينما كان العراقيون يعانون من ويلات الغزو والحروب من الطامعين في خيرات بلادهم كل فترة مما ركز لديهم شعور بالقلق وعدم الاستقرار والإيمان بأن كل شيء زائل ولا يبقى سوى الآلهة الخالدة. كما في النموذج (1، 3، 4). ومن الاستنتاجات: -التأكيد على الأعضاء التناسلية في التمثال أو التشفير الذي تبثه حركات الأيدي ما هي إلا علامات ذوات علاقة هامة في مدلولاتها بظاهرة الحمل والولادة لدى النسوة مما كان لها دور فاعل في الطقوس السحرية التشاكلية، ففي هذا الإنموذج تم التجسيد العميق لمجموعة من المفاهيم الفكرية المنتشرة في ذلك الوسط الاجتماعي القديم.
Generates human lives and take his life different paths It seeks to achieve the same through his activity and aspires to confirm its existence and differentiation within the total across the product idea and continuous effort in life, art one aspect of humanitarian action and a thought attributes is subject to the conditions and variables of the environment and society, but it remains part of the attempts to understand human existence and fate, and the artist and civilization breed and evolving under the pressure of the idea of life and death, which Tsanaan pattern of thought and civilization and creativity space as thinkers and creators who works with a view to understanding and access to secrets. So it summarized the problem of current research into the possibility to answer the following questions:- 1. How is understanding the dialectic of life and death in the arts of ancient civilizations? 2. What are the motives behind the artistic creations that celebrate life after death? 3. Do you have contributed to the arts in ancient civilizations in shaping the image of death and birth and cemented this image in ancient societies? The first chapter of the research has included a definition of the problem of research, the importance of research and the need for it has been identified as follows:- 1. The research placed the death and birth follow and how to deal with human and its role in the construction of ancient civilizations and how to use the death Kmoduah hired Architectural and Fine Arts. 2. offers a study of the assets placed in the birth and death of philosophical output. 3. offers a study of the assets placed in the birth and death of philosophical output. The search target has been identified. 1. Know the concept of life and death in ancient civilizations? Spatial- the border is determined by current research studying the ancient arts of the ancient Egyptian civilization of Iraq and civilization, and Greek civilization. Temporal border- is determined by current research study for the period from 3600 BC to 200 BC. M. Objectivity border - is determined by current research study architecture, sculpture and ceramics in ancient civilizations. The researcher analyzed the most important terms in the Find the second chapter included the first three sections represents a review of the historical roots of the idea of life and death in ancient civilizations. The second topic dealt with the myth and the idea of life and death the third section has included the study of representations of death and life in the arts of ancient civilizations. The third chapter contains research procedures were included, the research community and the selection of the sample and tool research and analysis of the amount of the sample (9) models. As the fourth quarter has resulted in the findings and conclusions, including the 1. realized the old Iraqi thought that it could not secure immortality and death as a fact crucial for all human beings, so it did not work for its own sake but also for others and for the principle of life itself. As in the form (1, 2). 2. His sense of the inevitability of death, a kind of sense of nihilism and anarchy nor the feasibility of life and often led to the feet of the ancient Iraqis to sacrifice cultural and architectural achievements of large collapsed and crashed not been preserved. 3. The ancient Egyptians felt safe, stability and tranquility in their distant fortified against the invaders while the Iraqis are suffering from the ravages of invasion and war of aspirants in the bounties of their country each period, which focused to have a sense of anxiety and instability and faith that everything is fleeting and only the immortal gods remains. As in the form (1, 3, 4). One of the conclusions:- 1. emphasis on the genitals in the statue or encryption which aired labor movements are only signs of animate important relationship in their meanings to the phenomenon of pregnancy and childbirth among women than have an active role in the magical rituals Alchaklah, in this model was deep embodiment of a group of intellectual concepts deployed in that the old social milieu.
Keywords: الفلسفة -- الجدلية -- الموت والحياة -- الحضارات القديمة -- حضارة العراق القديم -- الحضارة المصرية القديمة -- الحضارة الإغريقية